Consumption of processed cookies and the health risks for children (Research, Society and Development, 2025)
The consumption of industrialized filled cookies has become increasingly common among children, raising concerns about the impact of this habit on their health. These ultra-processed products contain high levels of added sugars, saturated fats, sodium, and food additives—factors associated with rising childhood obesity rates and other non-communicable chronic diseases (NCDs), such as hypertension and type 2 diabetes. This study aimed to analyze the potential harm of consuming these foods during childhood, based on information from products sold in supermarkets in the municipality of Machado (MG), Brazil. Data were collected from nutrition labels and ingredient lists, and then compared with current legislation (RDC No. 429/2020). The analysis revealed that, although the evaluated cookies comply with legal limits, their consumption still involves high amounts of sugars, saturated fats, and additives, which may pose health risks to children, especially when consumed in excess. Therefore, it is essential to reinforce the need for nutrition education, family guidance, and stricter regulation regarding the composition and marketing of these products, aiming to protect children’s health and promote healthier eating habits from an early age.